Penilaian gizi sederhana: alat penilaian praktis untuk menentukan status gizi pasien rawat inap di rumah sakit - Ida Mardalena; Bambang Suprapto; Widarto Widarto; Bhisma Murti (Jurnal Gizi Klinik Indonesia, 2005)
Background: Absence of effective and efficient screening tool for assessment of nutritional status have lead to high incidence of malnutrition among hospitalized patients.Objective: To develope practical screening tool for assessing nutritional status of hospitalized patients.Method: A simple method of nutritional assessment, called The Simple Nutritional Assessment, was compared to albumin serum as the gold standard. This study involved 50 nurses and 50 hospitalized patients in Dr. Moewardi General Hospital, Surakarta.Result: There was significant concordance of nutritional status assessed by the Simple Nutritional Assessment and the level of albumin serum (k=0,92). Sensitivity, specificity, and likelihood ratio of the Simple Nutritional Assessment compared to serum albumin were 92%, 67–75%, and 3.8, respectively. Internal consistence of the Simple Nutritional ssessment is high (Alpha=0.80). Average time required for doing the assessment was only 5 minutes.Conclusion: The Simple Nutritional Assessment can be used for quick screening of nutritional status of hospitalized patients with high sensitivity and reliability.